Learning geometry through M-Learning - Raya-Fernández, Álvaro; Sánchez-Cruzado, Cristina (Universidad de Alicante, 2022)
Mathematics education is key to the development of responsible future citizens, who must be able to understand and analyse their environment. To that end, using ICT we have proved a noticeable improvement in students´ attitudes towards mathematics, making them demonstrate a greater critical spirit, perseverance, precision and creativity, as well as an increase in their flexibility of thought (Garcia and Romero, 2009). We introduced m-learning methodology based on the use of mobile phones in classrooms, which takes advantage of their interest in technology and is closer to the students’ reality. This methodology gives them access to information without any spatial limitation, thus offering learning opportunities from beyond the classroom (Castro et al., 2016). Focusing on learning geometry, we used GeoGebra 3D, a virtual reality mobile app, which encourages them to create, manipulate and interact with geometric 3D models. We carried out an action-research in a second grade high school, with 28 students. We detected important deficiencies after an initial observation of students´ three-dimensional geometric knowledge. We developed a didactic mathematic proposal using m-learning, and we observed what was happened in the classrooms.
Keywords: Matemáticas - Estudio y enseñanza - Congresos; Geometría - Estudio y enseñanza - Congresos; Matemáticas - Enseñanza asistida por ordenador - Congresos; Geometry; M-Learning; Mathematical education